Penanaman Mangrove Sebagai Upaya Perluasan Ekosistem Pesisir di Peunaga Cut Ujong, Aceh Barat - Lisdayanti, Eka; Najmi, Nurul; Rahmawati, Rahmawati; Hasdanita, Fitry; Masrura, Delfian (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Damage to mangroves on the West Aceh coast due to the disaster tsunami and the increasing utilization of economic activities towards the beach area makes mangrove planting activities necessary. Service activities aim to support the benefits of conservation and expansion of mangrove ecosystems on the Coas of Peunaga Cut Ujong, Meurebo District, West Aceh Regency. This planting activity is a collaborative activity between industry players, academics, and the surrounding community which was initiated by PT MIFA Bersaudara as a form of concern for the environment and concrete action in contributing to coastal ecosystem conservation, especially for achieving the SDGs. The types of mangroves planted were Rhizophora apiculata and Rhizophora mucronate. This planting uses a planting method with artificial regeneration which involves planting seeds, propagules, or mangrove seedlings by moving the seedlings to a new location. Mangrove planting activities in Peunaga Cut Ujong managed to get attention and attention from the village community. Not only involved directly in mangrove planting activities but also committed to the maintenance and monitoring of the planted mangroves. In addition, the success of mangrove planting is also evident from the low mortality rate (5%) of the seedlings. The addition of more leaves, height, and mangrove roots that have begun to appear in some mangrove stands was observed seven months after planting.